Utilization Pattern of Crop Residues at Farm Level: Evidence from Diversified Rice-Based Cropping Systems in Bangladesh (Progressive Agriculture, 2013)
The study aims to examine the utilization of crop residues of 458 farm households covering four districts in Bangladesh. Primary data were collected during October to December 2012 through field survey following purposive sampling. The evidence showed that the average age of the respondents were 40.23 years with an average family size of 4.84. About 37.12% respondents had above primary level of education and 81% respondents were engaged primarily in agriculture. The average farm size was found to be 2.61 acre. The annual household income was found BDT 215,584 of which 75 and 25% came from agriculture and non-agriculture sources, respectively. The study areas were mostly dominated by rice based cropping systems. Among the crop, rice alone contributed 83.14% of the total cultivated land followed by vegetables (41.76%), pulses (39.08%) and jute with cropping intensities ranges from 153.16 to 282.12%. The whole retention of boro rice was found higher than aman rice and oilseeds and maize were found higher than all crops. No retention of crop residues was found in case of jute and pulses. It was indicated that the retention rate varied crop to crop as well as location to location. The distance had also another major factor on the retention of crop residues. The households were benefited from retention of crop residues by improving soil health, add soil nutrients, improving soil structure and increasing water conservation to the field. The crop residues were mostly used for animal feed followed by cooking fuel and add organic matter to the field. The used cooking fuel come from their own fuel wood (about 14-53%), own crop residues (about 10-25%) and from cowdung (about 4-22%), respectively. The sources of animal feed was found from own crops (about 3- 52%), own crop residues (about 16-18%) and from green grass (about 6-24%), respectively. The constraints to retention crop residues and uses were the lack of proper method of harvesting, transporting them to the house, deficit labor and uneconomic. Finally, the study suggests for conducting training on appropriate methods of harvesting, processing of retention crop residues and improvement of transportation of harvested crop at home properly.DOI: http://dx.doi.org/10.3329/pa.v23i1-2.16575Progress. Agric. 23(1 & 2): 111 122, 2012